TIR-only protein RBA1 recognizes a pathogen effector to regulate cell death in Arabidopsis - Nishimura, Marc T; Anderson, Ryan G; Cherkis, Karen A; Law, Terry F; Liu, Qingli L; Machius, Mischa; Nimchuk, Zachary L; Yang, Li; Chung, Eui-Hwan; El Kasmi, Farid; Hyunh, Michael; Osborne Nishimura, Erin; et al. (Proceedings of the National Academy of Sciences - PNAS, 2017)
Detection of pathogens by plants is mediated by intracellular nucleotide-binding site leucine-rich repeat (NLR) receptor proteins. NLR proteins are defined by their stereotypical multidomain structure: an N-terminal Toll-interleukin receptor (TIR) or coiled-coil (CC) domain, a central nucleotide-binding (NB) domain, and a C-terminal leucine-rich repeat (LRR). The plant innate immune system contains a limited NLR repertoire that functions to recognize all potential pathogens. We isolated Response to the bacterial type III effector protein HopBA1 ( ), a gene that encodes a TIR-only protein lacking all other canonical NLR domains. RBA1 is sufficient to trigger cell death in response to HopBA1. We generated a crystal structure for HopBA1 and found that it has similarity to a class of proteins that includes esterases, the heme-binding protein ChaN, and an uncharacterized domain of toxin. Self-association, coimmunoprecipitation with HopBA1, and function of RBA1 require two previously identified TIR-TIR dimerization interfaces. Although previously described as distinct in other TIR proteins, in RBA1 neither of these interfaces is sufficient when the other is disrupted. These data suggest that oligomerization of RBA1 is required for function. Our identification of RBA1 demonstrates that "truncated" NLRs can function as pathogen sensors, expanding our understanding of both receptor architecture and the mechanism of activation in the plant immune system.